«The four worlds of the Lake Geneva» or exploring the polysensoriality of landscape with visually-impaired people - Ernwein, M; Sgard, A (Consortium Érudit, 2012)
Geographical research on blindness and visual impairment tends to focus on the difficulties and fears of the visually-impaired, thus excluding them from other approaches to sensitivity and perception, such as landscape studies. However, the daily experiences of those with visual impairments are not limited to such feelings. In an attempt to go beyond the usual oculo-centrism in landscape studies, this paper describes our exploration with visually-impaired people of the extent to which they can be said to experience feelings about landscape, and come to reflect on the polysensoriality of their perception of landscapes.